In A State : an exhibition in Kilmainham Gaoi on national identity. - Project Arts Centre, Dublin (Dublin : Project Press, 1991)
Ballagh, Robert ; Cooke, Liadin ; Cross, Dorothy ; Cummins, Pauline ; Donnelly, Micky ; Duffy, Rita ; Foley, Marie ; Gingles, Graham ; Gleason, Gerry ; Graham, Patrick ; Hall, Patrick ; Kindness, John ; etc.
In A State : an exhibition in Kilmainham Gaoi on national identity, Project Arts Centre, Dublin, 1991
boek